2014
DOI: 10.1007/s10953-014-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the Like Dissolves Like Rule Hold for Fullerene and Ionic Liquids?

Abstract: Over 150 solvents have been probed to dissolve light fullerenes, but with a quite moderate success. We uncover unusual mutual polarizability of C 60 fullerene and selected room-temperature ionic liquids (RTILs), which can be applied in numerous applications, e.g. to significantly promote solubility/miscibility of highly hydrophobic C 60 molecule. We report electron density and molecular dynamics analysis supported by the state-of-the-art hybrid density functional theory and empirical simulations with a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 55 publications
3
74
0
Order By: Relevance
“…Chaban et al 35 proposed in a recent work the use of 1-butyl-3-methylimidazolium tetrafluoroborate, [BMIM][BF 4 ], ionic liquid for C60 dispersion, leading to solubilities, predicted using molecular dynamics simulations, as high as 66 g L −1 at 333 K. Results by Chaban et al 35 showed a strong charge transfer between the C60 and its solvation shell for imidazolium and pyridinium ILs, whereas this behavior is not present in the cases of ammonium and phosphonium ILs. Additional molecular dynamics simulation studies by Fileti 4 ] to enhance the dispersion of C60 in water solutions, which is of remarkable relevance for applications in the biomedical field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chaban et al 35 proposed in a recent work the use of 1-butyl-3-methylimidazolium tetrafluoroborate, [BMIM][BF 4 ], ionic liquid for C60 dispersion, leading to solubilities, predicted using molecular dynamics simulations, as high as 66 g L −1 at 333 K. Results by Chaban et al 35 showed a strong charge transfer between the C60 and its solvation shell for imidazolium and pyridinium ILs, whereas this behavior is not present in the cases of ammonium and phosphonium ILs. Additional molecular dynamics simulation studies by Fileti 4 ] to enhance the dispersion of C60 in water solutions, which is of remarkable relevance for applications in the biomedical field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5,6 In this work, its BE IL-C60 = 10.66 kcal mol -1 , which can be considered as a low limit from which larger BE IL-C60 could be a good starting point for the search of new ILs with improved solvation features.…”
Section: Ils Based On [Be] and [Sa] Anionsmentioning
confidence: 94%
“…Fileti et al 8 have hypothesized, using computational chemistry approaches, that the solubility of C 60 in room temperature ionic liquids (ILs), based on imidazolium cation and tetrafluoroborate anion, is higher than those previously reported in other traditional solvents, 5 and thus, opening a new way for C 60 solubilization.…”
Section: Andmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,[9][10][11][12][13][14][15][16][17][18][19][20] The physical chemical properties of ILs are important for capturing toxic gases, separation applications through biphasic systems, solubilization of nanoscale entities, such as nanotubes and fullerenes. [1,12,13,[21][22][23] Amino acid (AA) ionic liquids (AAILs) are a relatively new research field. [24] They can be obtained from amino acids and bulky cations, such as imidazolium-based and phosphonium-based ones.…”
Section: Introductionmentioning
confidence: 99%